The global human settlement layer sets a new standard for global urban data reporting with the urban centre database - Melchiorri, Michele (Frontiers in Environmental Science, 2022)
Monitoring of sustainable development goals (SDGs) requires a wealth of updated, reliable, and comparable data on planet Earth with respect to societal activities and society–environment interactions. Despite the massive big-data archives available today, salient data are missing for key thematic domains and geographical areas. Even for cities, which are the most prominent manifestations of human agglomeration, the data are scarce, sectoral, and scattered. Earth observation may help reconcile the disparities between data-rich and data-poor territories. The Global Human Settlement Layer (GHSL) project of the European Commission has generated an open-source global dataset on cities—the GHSL Urban Centre Database (GHS-UCDB). This database describes more than 10,000 Urban Centres in 2015, with their locations, extent, and sets of geographical, socio-economic, and environmental attributes, as well as multi-temporal data records (covering a time span of up to 40 years) (Figure 6). The database combines information extracted from satellite imagery with physical and socio-economic information from several voluminous and heterogeneous sources provided by researchers and institutions as open geospatial data. The paradigm introduced with the GHS-UCDB relies on massive geospatial data integration and harmonisation conducted in the GIS environment (mainly via spatial joins and zonal statistics). The range and depth of geospatial and statistical variables in this dataset represent a new standard foundation for information on cities—more than doubling the number of cities usually reported by international organisations and offering the capacity to understand dynamics, e.g., on population, greenness, economic productivity, night-time light, and pollutant emissions. Moreover, the database offers the basis to estimate SDG indicators and other essential variables for the Post 2015 Development Agenda.